(untitled) (Research, Society and Development, 2024)
Efficient electricity management poses a growing challenge for both public and private sectors. Understanding available mechanisms can significantly curb unnecessary consumption. Nudge theory, based on behavioral economics, aims to positively shape individual behavior through information architecture, while Captology explores how technology can guide users towards desired behaviors and the synergy between these sciences can generate solutions. To this end, this study investigates nudge-based interventions to reduce electricity consumption using the systematic mapping of Kitchenham, Budgen and Brereton (2015). Google Scholar was queried from April to July 2023 with ("nudges" OR "green nudges" AND "electricity"). Out of 365 identified articles, 17 were selected after analysis. Most were published in 2022, with Science Direct contributing the highest number. The reviewed studies span diverse sectors—business, residential, hotel, school, administrative, and academic—largely in the private sector. Interventions leveraging feedback, incentives, and social norms prove effective in curbing electricity use. Technologies such as Smart Plugs, Smart Meters, Submeters, and web-based systems feature prominently. In conclusion, while some studies explore emerging technologies, there remains a gap in thoroughly analyzing their potential to robustly drive nudging strategies for behavioral changes in electricity consumption.